Calculation and design of Power Split Device on A Hybrid Vehicle - Tran Thanh An; Duong Quang Minh; Nguyen Van Tuan (Journal of Applied Science and Engineering, 2024)
Hybrid car technology is a combination of the advantages of pure electric cars and fossil fuel cars. Due to the electric motor (EM) support, the internal combustion engine (ICE) does not have to work in inefficient areas, saving fuel and reducing environmental pollution. However, to distribute the right source of motivation and the working mode, the role of the coordinator is vital. This paper aims to calculate the combination of two power sources from the EM and the ICE on hybrid cars. After calculating the design, the calculation and strength test of the power combiner was carried out using Ansys software. Results of this study showed that the maximum stress on the ring gear, sun gear, planetary gear, and the shaft is 160.89 Mpa, 175.56 Mpa, 239.03 Mpa, and 415.56 Mpa, respectively, and the maximum deformation on the ring gear, sun gear, planetary gear, and the shaft is 0.0104 mm, 0.017 mm, 0.0184 mm, and 0.178 mm, respectively. This shows that the article’s results can be used in research on the Power Split Device in Hybrid cars.